Cholesterol oxidation between health and disease - Poli, Giuseppe (Henry Stewart Talks, 2020)
Enzymatic and non-enzymatic oxidation of cholesterol, Increased amount of plasma oxysterols in hyper cholesterolemia, Pathogenesis of atherosclerosis, Alzheimer’s disease, inflammatory bowel disease, Physiological role of oxysterols of enzymatic origin in: membrane structure and function, synthesis of steroid hormones and bile acids, Antiviral effects of side-chain oxysterols